EFL Female Teachers’ and Students’ Experiences of Gender Discrimination in Rural Nepali Schools - Neupane, Binod (English Language Teaching Perspectives, 2022)
Gender discrimination in schools is a serious problem in developed and developing countries including Nepal. Literature shows that gender discrimination in educational institutions, like in other workplaces, is common. My experience as a teacher and the cross-road conversation with some EFL female teachers and students triggered me to study the issue of gender discrimination in schools critically. The purpose of the study reported here was to explore EFL female teachers' and students' experiences of gender discrimination in Nepali schools. Using qualitative phenomenology design, I collected information through semi-structured interviews with eight female teachers and eight students from four schools in a district. The result showed that many female teachers and girls experienced various forms of gender-based discrimination such as psychological and emotional torture, sexual harassment, inequality in assigning roles and responsibilities, discrimination in hiring, unequal wages, disrespect, gender-based bias in grading, and lack of gender-inclusive curriculum and textbooks in schools. Similarly, the paper suggests the teachers and the stakeholders develop gender-inclusive curricula and promote positive gender socialization for gender equality in schools.